Effect of Parenting Styles on the Students’ Academic Performance in Senior Secondary Schools in Northern Division, Mbale City. A Case Study of Nkoma Senior Secondary School - Sandra Nabukenya (Uganda Christian University, 2024)
This study was about the effect of parenting styles on the students’ academic performance of senior secondary schools in NORTHERN Division, Mbale City a case study of Nkoma Senior Secondary School. The study was guided by the following objectives; to determine the effect of authoritative parenting on students’ academic performance of senior secondary schools in NORTHERN Division, Mbale City a case study of Nkoma Senior Secondary School, to examine the extent to which Permissive Parenting style influences students’ academic performance of senior secondary schools in NORTHERN Division, Mbale City a case study of Nkoma Senior Secondary School, to establish the how Neglectful Parenting influences students’ academic performance of senior secondary schools in NORTHERN Division, Mbale City a case study of Nkoma Senior Secondary School, The study used a descriptive research design. The sample size was got from a total population of 120 people, The sample size was 92 people using self-administered questionnaires for both quantitative and qualitative methods and interview checklist. This chapter presents findings effect of parenting styles on the students’ academic performance in senior secondary schools in NORTHERN division, mbale city, The respondents were asked to indicate their Sex, Age, Highest academic qualification, marital status, position and their religion , the research instruments used for data collection were relevant as they analyzed the data and ensured reliability and validity of the findings got from the study area, the study focused on the effect of parenting styles on the students’ academic performance in senior secondary schools in NORTHERN division, mbale city. The researcher concludes that the effect of authoritative parenting on students’ academic performance in senior secondary schools is a critical area of research that underscores the significance of parenting styles in shaping educational outcomes. This study has examined the relationship between authoritative parenting characterized by high responsiveness and high demands and students' academic performance. In conclusion, the evidence underscores that authoritative parenting is a key factor in fostering academic success among senior secondary school students. By promoting authoritative parenting practices, educational stakeholders can contribute to improved academic outcomes and overall student development.